Agreement between the United Kingdom of Great Britain and Northern Ireland and the Grand Duchy of Luxembourg on the Participation in Certain Elections of Nationals of Each Country Resident in the Territory of the Other, Luxembourg, 18 June 2019. ([2019-07-04]) - Unknown
No abstract available